Effect of loading type on RC T-Beam sections involving construction errors - Elsaid Abdallah Bayoumi (Journal of Civil Engineering, 2022)
The paper presents the effect of loading type on RC T-beam sections involving construction errors. This study involved 12 RC T- beams specimens divided into two main categories according to loading method. First category were loaded with uniformly distributed load at two-edges of slab while the second, were loaded with two-point concentrated loads at the middle length of beam specimen. The aim of this study is to evaluate, the effect of malposition of slab reinforcement, unequal configuration of slab reinforcement and change in bar diameter of slab reinforcement on the structural behavior of T-beam sections. The results indicated that malposition of slab reinforcement leads to a lower bending moment capacity of the slab. Flexural capacity of T-beams were higher than the rectangular beams where part of slab contributes to the resistance of the loads. Well-arranged distribution of reinforcement improves the ductile behavior of the slab and reduces the corresponding deflections.